2016
DOI: 10.1002/polb.24118
|View full text |Cite
|
Sign up to set email alerts
|

Green solvent approach for printable large deformation thermoplastic elastomer based piezoresistive sensors and their suitability for biomedical applications

Abstract: Composites based on biocompatible thermoplastic elastomer styrene‐ethylene/butylene‐styrene (SEBS) as matrix and multi‐walled carbon nanotubes (MWCNT) as nanofillers show excellent mechanical and piezoresistive properties from low to large deformations. The MWCNT/SEBS composites have been prepared following a green solvent approach, to extend their range of applicability to biomedical applications. The obtained composites with 2, 4, and 5 wt % MWCNT content provide suitable piezoresistive response up to 80% de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
73
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(82 citation statements)
references
References 52 publications
8
73
1
Order By: Relevance
“…As observed, the mechanical hysteresis of the films increases with increasing applied strain, demonstrating the increase of the dissipated energy. This behavior has been reported for CNT/elastomer composites [30] and is related to the slow relaxation dynamics of the polymer chains during the unloading cycle.…”
Section: Mechanical Characterizationsupporting
confidence: 74%
See 1 more Smart Citation
“…As observed, the mechanical hysteresis of the films increases with increasing applied strain, demonstrating the increase of the dissipated energy. This behavior has been reported for CNT/elastomer composites [30] and is related to the slow relaxation dynamics of the polymer chains during the unloading cycle.…”
Section: Mechanical Characterizationsupporting
confidence: 74%
“…In this work, carbon nanotubes have been incorporated in the SELP matrix in order to obtain nanocomposite films endowed with improved piezoresistive response that can find potential use across a wide range of biotechnological areas, including also sensor and actuator applications. A large number of studies report the development piezoresistive sensors based on CNTs with synthetic polymers such as styrene-butadiene-styrene (SBS) [30], poly(vinyl alcohol) (PVA) [31] and polyvinylidene fluoride (PVDF) [32] and also conductive blends such as polyaniline/styrene-butadiene-styrene (PANI/SBS) [33]. However, no studies have previously reported the development of piezoresistive materials based in a semiconductor and genetically engineered protein polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Among the different polymer families, thermoplastic elastomers (TPEs) and elastomers present specific mechanical properties. Their larger deformation and easy recovery capabilities combined with their low cost and ease of processing make these materials appropriate for soft applications such as robotics, artificial skin and muscles, pressure sensors, SHM sensors, and biomedical devices [17,18]. TPEs combine the mechanical properties of elastomers with the chemical stability and processability of thermoplastics, without the need of vulcanization steps [18].…”
Section: Introductionmentioning
confidence: 99%
“…Soft polymer, including PDMS and rubbers, styrene-butadiene-styrene (SBS) and their related copolymer are best options for developing piezoresistive sensors [142,143]. Particularly, among the SBS family, apart from the beneficial attributes as mentioned, SEBS has demonstrated high stretchability (i.e., deformation strain can range from less 1% to 50%), excellent endurance, elastic recovery and resistance to harsh environmental conditions [144][145][146][147].…”
Section: Gn Epoxymentioning
confidence: 99%